2016
DOI: 10.5606/tftrd.2016.77861
|View full text |Cite
|
Sign up to set email alerts
|

Balance performance and fear of falling in older patients with diabetics: a comparative study with non-diabetic elderly

Abstract: Objectives: This study aims to evaluate balance performance and fear of falling (FOF) in older people with and without diabetes mellitus (DM) and the parameters affecting balance and FOF in older patients with DM. Results: Timed Up and Go test, BDI, BAI, and FES-I scores were significantly higher; BBS, OLST, and MBI scores were significantly lower in patients. There were significant effects of neuropathic pain, hypertension and cardiovascular disease on BBS and FES-I in diabetic patients. One-Legged Stance tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Based on our study, the mCTSIB can sufficiently differentiate the degrees of balance impairment in the ODM. Poor postural control observed in the ODM is the result of sensory and motor deficits associated with microvascular complications of DM as well as FoF [11][12][13]25]. A significant decrease in the mCTSIB-Tol score and the failed performances on the mCTSIB suggest an increase in the degrees of balance impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our study, the mCTSIB can sufficiently differentiate the degrees of balance impairment in the ODM. Poor postural control observed in the ODM is the result of sensory and motor deficits associated with microvascular complications of DM as well as FoF [11][12][13]25]. A significant decrease in the mCTSIB-Tol score and the failed performances on the mCTSIB suggest an increase in the degrees of balance impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a significant risk factor for falls in older adults [7][8][9][10] and associated with an increase in FoF [11]. The prevalence of falls and FoF is significantly higher in older adults with DM (ODM) than in older adults without DM (ONDM) [8,[11][12][13][14]. Microvascular complications associated with DM result in multiple impairments including sensory deficits and muscle weakness due to peripheral neuropathy [15][16][17][18], loss of visual acuity due to retinopathy [18][19][20], and impaired postural control and falls due to vestibulopathy [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear of falling (Falls Efficacy Scale-International (FES-I)), neuropathic pain [leeds assessment of neuropathic symptoms-signs (lanss), mobility [timed up and go test (tug)], balance [berg balance scale (bbs)], one-legged stance test (olst), disability status [modified barthel index (mbi)], depression [beck depression inventory (bdi)] and anxiety [beck anxiety inventory (bai)] was assessed. They concluded that in older patients with DM, fear of fall is increased and they have more balance disturbances compared to age matched individuals without DM [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another description has referred to FOF as a patient's loss of confidence in his or her balance abilities (9). Patients with DM may have balance problems and FOF (10). The FOF decreases willingness to mobility leading to decrease exercise and/or physical activity which are effective methods for controlling blood glucose.…”
Section: Introductionmentioning
confidence: 99%